2021
DOI: 10.1111/jocs.15794
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socioeconomic status in patients with left ventricular assist devices (LVADs)

Abstract: Background: Socioeconomic status (SES) can be a powerful predictor of adverse outcomes among heart failure patients but its impact on survival and readmission following left ventricular assist device (LVAD) implantation surgery is poorly understood. We investigated if the LVAD recipients from more deprived neighborhoods experienced higher mortality and readmission rate after device implantation as compared to those from less deprived areas.Methods: This is a single center, retrospective analysis evaluating adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In previous studies regarding socioeconomic status and clinical outcomes among patients with LVADs, socioeconomic status did not affect mortality, [33][34][35][36] nor survival or delisting on the heart transplant waiting list. 37 Conflicting results have been reported regarding hospital readmission, [33][34][35]38 The literature suggests that the careful selection of LVAD candidates, pre-LVAD optimization regarding patients' medical, behavioral, and psychosocial needs, and effective LVAD management program may mitigate poor clinical outcomes among those with low socioeconomic status. 33,35,36 Moreover, follow-up care that is organized and structured with frequent visits and time to address worries about medications and improve self-efficacy may improve medication adherence.…”
Section: Lvad: Ventricular Assist Devicementioning
confidence: 69%
See 1 more Smart Citation
“…In previous studies regarding socioeconomic status and clinical outcomes among patients with LVADs, socioeconomic status did not affect mortality, [33][34][35][36] nor survival or delisting on the heart transplant waiting list. 37 Conflicting results have been reported regarding hospital readmission, [33][34][35]38 The literature suggests that the careful selection of LVAD candidates, pre-LVAD optimization regarding patients' medical, behavioral, and psychosocial needs, and effective LVAD management program may mitigate poor clinical outcomes among those with low socioeconomic status. 33,35,36 Moreover, follow-up care that is organized and structured with frequent visits and time to address worries about medications and improve self-efficacy may improve medication adherence.…”
Section: Lvad: Ventricular Assist Devicementioning
confidence: 69%
“…37 Conflicting results have been reported regarding hospital readmission, [33][34][35]38 The literature suggests that the careful selection of LVAD candidates, pre-LVAD optimization regarding patients' medical, behavioral, and psychosocial needs, and effective LVAD management program may mitigate poor clinical outcomes among those with low socioeconomic status. 33,35,36 Moreover, follow-up care that is organized and structured with frequent visits and time to address worries about medications and improve self-efficacy may improve medication adherence. 39 This may also explain why we did not observe a difference in medication use and adherence.…”
Section: Lvad: Ventricular Assist Devicementioning
confidence: 99%
“…Among patients bridged to HT with a durable LVAD between 2004 and 2014, SES was not associated with waitlist outcomes although post-transplant outcomes were worse in the lowest SES quartile compared to the remaining quartiles.6 Regarding LVAD outcomes, single centers studies demonstrated that SES had limited to non-significant effects on post LVAD outcomes. [7][8][9] We expand on these findings from a larger national cohort to further highlight lack of association between SES and in-hospital outcomes during index LVAD and HT hospitalizations in the current era.…”
Section: Discussionmentioning
confidence: 91%
“…Another study showed that low SES might not affect the clinical course after LVAD implantation (60). The readmission ratio was also not changed by the low SES (61). SES does not independently impact the survival and readmission after HeartWare HVAD and Heartmate III LVAD implantation.…”
Section: Left Ventricular Assist Devicementioning
confidence: 99%